2023
DOI: 10.1039/d3cp02644b
|View full text |Cite
|
Sign up to set email alerts
|

Interface plasmon damping in the Cd33Se33/Ti2C MXene heterostructure

Junais Habeeb Mokkath

Abstract: Energy band diagram and transition contribution map of the Cd33Se33/Ti2C heterostructure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…45–52 In recent years, considerable progress has been achieved in theoretical investigations utilizing real-time time-dependent density functional theory (rt-TDDFT) 53–62 simulations to gain insights into the generation and distribution of HCs. 63–69 It is noteworthy that first-principles studies have been used to conduct extensive research on HC processes. For instance, studies on the HC transfer between Ag, Au, and Cu nanoparticles that interact with CO molecules have shown that electron generation within CO decreases non-monotonically as plasmon decay increases.…”
Section: Introductionmentioning
confidence: 99%
“…45–52 In recent years, considerable progress has been achieved in theoretical investigations utilizing real-time time-dependent density functional theory (rt-TDDFT) 53–62 simulations to gain insights into the generation and distribution of HCs. 63–69 It is noteworthy that first-principles studies have been used to conduct extensive research on HC processes. For instance, studies on the HC transfer between Ag, Au, and Cu nanoparticles that interact with CO molecules have shown that electron generation within CO decreases non-monotonically as plasmon decay increases.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting avenue of research is the excited state dynamics and energy transfer processes between metal NPs and adsorbed molecules under various conditions. In this context, the strong coupling regime is especially promising, since the initial eigenstates become thoroughly mixed, which leads to the formation of new energy states and potentially favorable electron transition possibilities . These changes of the electronic landscape yield modifications of reaction pathways, allowing for modified chemistry, catalytic applications, or enhanced selectivity .…”
Section: Introductionmentioning
confidence: 99%
“…These changes of the electronic landscape yield modifications of reaction pathways, allowing for modified chemistry, catalytic applications, or enhanced selectivity . When two moieties are placed in close proximity and are energetically tuned to each other’s transitions, as is the case in the strong coupling regime, resonance energy transfer occurs, which can aid in the extraction of hot carriers generated during plasmon decay in plasmonic-molecular systems. , This macroscale coupling thus becomes an important tool in tailoring excited-state properties, such as hot carrier transfer across metal–semiconductor interfaces , or to an adsorbed molecule. , Polariton modification of energy transport is also observed at lower energies in the vibrational regime by coupling molecules to macroscopic Fabry–Perot cavities. This is enabled by the additional photonic degrees of freedom which mediate interactions between molecules, leading to additional electron–electron correlations over large distances .…”
Section: Introductionmentioning
confidence: 99%
“…44,45 This allows one to treat uniformly the whole system, enabling quantification of effects related to modifications of the matter subpart in the excited state that are inaccessible by classical quantum optical and electromagnetic methods. Such an approach is beneficial in the study of plasmon-mediated processes such as hot carrier transfer across metal–semiconductor interfaces 46,47 or to an adsorbed molecule, 48,49 differentiation between charge-transfer and localized surface plasmon resonance (LSPR), 45 or plasmon-assisted electrocatalysis for CO 2 reduction. 50 Hence, TDDFT offers the possibility of investigating the interplay of shape, material, orientation, and chemical species on plasmon–adsorbate interactions, here specifically in the strong coupling regime.…”
Section: Introductionmentioning
confidence: 99%